Expresivitatea limbajului popular în romanul haiducesc „Iancu Jianu, zapciu de plasă” și „Iancu Jianu, căpitan de haiduci” de Nicolae D. Popescu: The expressivity of popular language in the hajduk novels ”Iancu Jianu, Head of Administration” and ”Iancu Jianu, Captain of the Hajduks” by Nicolae D. Popescu - Rat, Ileana Manuela (Swedish Journal of Romanian Studies, 2021)
This paper analyzes the expressivity of popular language from the novels ”Iancu Jianu, Head of Administration” and ”Iancu Jianu, Captain of the Hajduks” by N.D. Popescu. The popular language is a language specific aspect, a language version and a main component of the oral version of the national language. In literary works, the popular language has a stylistic purpose. The aesthetic value of the text is the result of the process by which the expressiveness of the writer`s language is converted into an individual literary rule. The stylistic processes and brands encountered in popular language are national specific and they reflect the history, the way of thinking and the feelings of Romanian people. The popular language implies the release of constraints and limitations imposed by national language standard. I have chosen this study because it is an important matter that was not explored in Romanian hajduk novels and hajduk short fiction (novella, short-story, and tale).